IMPACT OF KIPI COMPANY DEVELOPMENT IN TANAH KUNING - Atikah, Nur; Adi; al amrie, machmud (Jurnal Ekonomi Pembangunan dan Manajemen, 2023)
The development of a company in an area can bring both positive and negative impacts. This document aims to provide an abstract on the potential impacts of building a company, specifically on land in the Kuning area. Firstly, it is important to note that land development for commercial purposes can lead to economic growth and job opportunities. The company itself may provide employment opportunities for the local community, as well as attract other businesses and investments to the area. This can lead to an increase in income levels and a boost in the overall economy of Kuning. However, the development of a company on land may also have negative consequences, particularly on the environment. The construction process may involve deforestation, pollution of air and water sources, and destruction of wildlife habitats. Additionally, the continuous operation of the company may lead to increased traffic, noise pollution, and waste production. Furthermore, the presence of a company on land can also have social impacts. It may cause displacement of local communities or changes in their way of life. This can result in cultural conflicts and loss of traditional practices. The influx of new employees and potential gentrification may also cause changes in the social dynamics of the area. In conclusion, while the development of a company on land in Kuning may bring economic benefits, it is important to carefully consider its potential impacts on the environment and society. Measures must be taken to mitigate any negative effects and ensure sustainable development for both the company and the community. This abstract serves as a brief overview of the possible consequences and highlights the importance of responsible decision-making when it comes to land development for commercial purposes. So, it is important for stakeholders to conduct thorough research and engage in open communication with local communities before proceeding with any project. By doing so, we can strive towards achieving balance between economic growth and environmental sustainability in Kuning.